COASTAL COMMUNITY DEVELOPMENT MODEL BASED ON NON-FORMAL EDUCATION TO OPTIMIZATION POSDAYA (FAMILY EMPOWERMENT POS) - Tri Joko Raharjo; Tri Suminar (JOURNAL OF EDUCATION SCIENCE, 2015)
The purpose of research to describe the application of optimization programs empowerment fishing families in the district Wedung Demak on the field's Health, education, social, cultural and economic as well as describing its effectiveness in reducing poverty. Design research is a practical action (practical action research). The location of research is in the District Wedung Posdaya District of Demak. The primary resource is fishing families involved in target Posdaya, informal and non-formal community leaders. Collecting data by interview and observation. The validity of the data with confidence, perseverance, and honesty. Qualitative research data analysis with interactive model. The results showed empowerment fishing families with garbage bank program, early childhood parenting, family counseling aware of nutrition, marketing management training fish jerky products through packaging and product quality, assessed effectively empower families of fishermen. Fishing families have the opportunity to participate in development in the areas of health, education, economic and socio-cultural values are clean and healthy, so that they can improve a clean and healthy lifestyle, become self-sufficient families and families who can increase his income.Keywords:Coastal Community Empowerment Model, Family Empowerment Post, Non-formal Education